Endotoxins in surgical instruments of hip arthroplasty - Vania Regina Goveia; Isabel Yovana Quispe Mendoza; Gilberto Lima Guimarães; Flavia Falci Ercole; Bráulio Roberto Gonçalves Marinho Couto; Edna Marilea Meireles Leite; Maria Aparecida Resende Stoianoff; José Antonio Guimarães Ferreira (SciELO, 2016)
Abstract OBJECTIVE To investigate endotoxins in sterilized surgical instruments used in hip arthroplasties. METHOD A descriptive exploratory study conducted in a public teaching hospital. Six types of surgical instruments were selected, namely: acetabulum rasp, femoral rasp, femoral head remover, chisel box, flexible bone reamer and femoral head test. The selection was based on the analysis of the difficulty in removing bone and blood residues during cleaning. The sample was made up of 60 surgical instruments, which were tested for endotoxins in three different stages. The EndosafeTM Gel-Clot LAL (Limulus Amebocyte Lysate method) was used. RESULT There was consistent gel formation with positive analysis in eight instruments, corresponding to 13.3%, being four femoral rasps and four bone reamers. CONCLUSION Endotoxins in quantity ≥0.125 UE/mL were detected in 13.3% of the instruments tested.